2015
DOI: 10.1186/s12967-015-0699-2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic helix B peptide inhibits ischemia reperfusion-induced renal fibrosis via the PI3K/Akt/FoxO3a pathway

Abstract: Renal fibrosis is a main cause of end-stage renal disease. Clinically, there is no beneficial treatment that can effectively reverse the progressive loss of renal function. We recently synthesized a novel proteolysis-resistant cyclic helix B peptide (CHBP) that exhibits promising renoprotective effects. In this study, we evaluated the effect of CHBP on renal fibrosis in an in vivo ischemia reperfusion injury (IRI) model and in vitro TGF-β-stimulated tubular epithelial cells (TCMK-1 and HK-2) model. In the IRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…The present study demonstrated that a single dose of CHBP, plasma half-life 300 min, (Yang et al, 2014b) administrated 15 min after reperfusion greatly ameliorated renal IR injury at the early stage of 48 h. This result was consistent with the evidence that a single dose of CHBP protected the kidney from IR injury at 12-week (Yang et al, 2015c). Linear HBSP, plasma half-life about 2 min, administered at 1 h, 6 h and 12 h protected the kidney against IR injury at 24 h (Brines et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study demonstrated that a single dose of CHBP, plasma half-life 300 min, (Yang et al, 2014b) administrated 15 min after reperfusion greatly ameliorated renal IR injury at the early stage of 48 h. This result was consistent with the evidence that a single dose of CHBP protected the kidney from IR injury at 12-week (Yang et al, 2015c). Linear HBSP, plasma half-life about 2 min, administered at 1 h, 6 h and 12 h protected the kidney against IR injury at 24 h (Brines et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…In the IR kidney, CHBP reduces endoplasmic reticulum stress and increases autophagy (Yang et al, 2014b), leading to less apoptosis (Kaushal and Shah 2016). CHBP also ameliorated renal in ammation and reduced chronic deposition of extracellular matrix through inactivating forkhead box O 3a (FoxO3a) after IR (Yang et al, 2015c). Nevertheless, the exact underling mechanism in the renoprotection of CHBP is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Increased Akt signaling is associated with suppression of cell apoptosis and promotion of renal fibrosis in IR injuryinduced acute kidney injury (84). However, suppression of Akt phosphorylation accelerates tubular repair and inhibits renal fibrosis (85).…”
Section: Epo and Autophagymentioning
confidence: 99%
“…Ischemia reperfusion (IR)‐induced AKI is common in clinical practice, can lead to renal fibrosis, and is an important risk factor for chronic kidney disease (CKD). Although a large amount of evidence has confirmed the progression from IR‐induced AKI to subsequent kidney fibrosis (Kim & Padanilam, ; Yang et al, ), the molecular mechanism of AKI‐induced renal fibrosis has yet to be understood. Thus, identifying effective drug treatments for this disorder has important clinical significance.…”
Section: Introductionmentioning
confidence: 99%